One year later: The effect of changing azole-treated bulbs for organic tulips bulbs in hospital environment on the azole-resistant Aspergillus fumigatus rate. (4th March 2021) - Rocchi, Steffi; Godeau, Chloé; Scherer, Emeline; Reboux, Gabriel; Millon, Laurence
Abstract: Azole-treated plant bulbs have already been evoked as a potential explanation of the worldwide spread of azole-resistant Aspergillus fumigatus (ARAf). We previously pointed out the presence of a high rate of ARAf (71% of A. fumigatus detected on azole-supplemented media) in flower beds containing azole-treated bulbs at the hospital's surroundings. We show here that planting organic bulbs can be a solution to reduce ARAf burden (from 71% rate to below 3%). The results suggest that replacing treated bulbs with organic bulbs may be sufficient to regain a population that is predominantly susceptible in just 1 year. Lay Summary: Antifungal resistance is increasingly observed in fungal pathogens . This study argues that planting organic bulbs in hospitals' outdoor surroundings could be a good alternative to continue to beautify green spaces, without the risk of dissipating antifungal-resistant fungal pathogens.